Iron Oxide Nano-Adsorbent Doped with Nickel and Palladium for Phosphorus Removal from Water - Casagrande-Denardin, J (Royal Society of Chemistry, 2025)
Excessive phosphorus (P) in surface and ground water can cause serious environmental issues. This study aims to synthesize and characterize novel iron oxides (FexOy) nanoparticles (NPs) with and without Ni and Ni-Pd doping and unravel the NPs performance and mechanism for P removal from water. X-ray diffraction, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy results confirmed successful doping of Ni and Ni-Pd on FexOy NPs. FexOy-Ni NPs exhibited a higher specific surface area and isoelectric point than FexOy and FexOy-Ni-Pd NPs. The kinetic data for P adsorption on FexOy NPs fitted to the pseudo-first order model and FexOy-Ni and FexOy-Ni-Pd NPs fitted to the pseudo-second order model. Adsorption isotherm data for FexOy NPs fitted to the Freundlich model and FexOy-Ni and FexOy-Ni-Pd NPs fitted to the Langmuir model. The maximum P adsorption capacity was the highest for FexOy-Ni (35.66 mg g−1) followed by FexOy-Ni-Pd (30.73 mg g−1) and FexOy NPs (21.97 mg g−1), which was opposite to the P desorption order of these adsorbents. The adsorption and characterization analysis suggested that inner-sphere complexes and co-precipitation were the key mechanisms for P adsorption on FexOy-Ni and FexOy-Ni-Pd NPs. Therefore, FexOy-Ni NPs were a highly effective adsorbent for removing P from water. © 2025 The Royal Society of Chemistry.